Determinants of Effective Knowledge Transfer in Public Health: A Case Study - Ong, Lea Szu (2017)
Public health organizations has been known as learning organization and are usually knowledge-based where they strive to make better use of their accumulated knowledge internally and externally. Disjointed pieces of raw knowledge has to be converted into actionable knowledge however, it must also be shared and transferred to the right entities as well as ensuring it is being used. Therefore effective knowledge transfer is crucial in providing the capacity for such organization. The purpose of this study is to discover the determinants of effective knowledge transfer in a public health organization. Using a qualitative research approach, this research employed a case study of a public health organization and used semi-structured interviews as the main data collection tool. The purposive sampling technique was used to select the sample. A semi-structured interview guide was used for data collection. The data was analysed using the thematic analysis technique. The study found that are the characteristics of the knowledge source, characteristics of the knowledge transferred, information technology, the organization context, characteristics of the knowledge recipient and the extent of effective communication as the key determinants influencing knowledge transfer in the case study.